Runoff and soil loss from steep sloping vineyards in the Douro Valley, Portugal: rates and factors - Figueiredo, Tomás de (2013)
The Douro Region,, NE Portugal, where the grapes for Port Wine are produced, faces a high potential erosion risk due to its natural setting, for long tackled with heavy labour inputs. These allowed the stabilization of steep vineyard covered hill-slopes by means of traditional terracing, manually built and following models that changed through time. Alternative vineyard installation and cultivation techniques were tested and progressively adopted, namely row plantation perpendicular to the contour, nowadays an integral yet small part of the plantation schemes accepted under the rules of the World Heritage status, granted by UNESCO in 2001. This paper investigates the effects of vine plantation schemes on long-term (10 years) runoff and soil loss data recorded in the Douro Region using a set of meso-scale erosion plots installed in vineyards planted in rows perpendicular to the contour. It also aims at identifying, and quantitatively deriving the significance of erosion factors helping to interpret the results obtained. Runoff and soil loss were measured between 1978 and 1988 using five runoff plots, 32.1 m long and 5.2 m wide, on a 45 % slope, over a silt loam soil containing 60 % rock fragments by mass, under Mediterranean climatic regime with less than 600 mm mean annual rainfall. Vine plantation schemes tested correspond to three different plant densities (3571, 4808, 5917 plants ha-1) on paired plots (except for the intermediate plant density, tested in a single plot), which provided a mean vegetation cover of 50, 60 and 75 %. The 10 year data analyzed correspond to 167 runoff events. Mean annual runoff and soil loss, computed for the 10 years of records, were 22 mm and 361 kg ha-1 respectively. These relatively low soil loss rates are explained under the prevailing conditions of rainfall erosivity, soil, topography and vegetation cover, by the very high rock fragment cover, protecting the topsoil from wash by runoff. Soil loss was very much concentrated in a few erosive events, 3 of them being responsible for ca.75 % of the total soil loss recorded in 10 years. These events occurred in spring and summer, whereas most erosive events in Mediterranean conditions occur in autumn and winter. Results also show that increasing the vine plant density by 66 % resulted in a reduction of mean annual runoff by 19 % and of mean annual soil loss by 57 %, demonstrating the significant effect of this erosion control measure in permanent crops such as vineyards.